Potential action of androstenedione on the proliferation and apoptosis of stromal endometrial cells - Anido Mabel; Bacallao Ketty; Clementi Marisa; Quezada Susana; Maliqueo Manuel A; Johnson Cecilia; Vega Margarita (BMC, 2004)
Abstract Background Hyperandrogenic conditions have been associated with a high prevalence of endometrial pathologies related to cell survival. However, the action of androgens on proliferation and apoptosis in endometrial cells is poorly understood. Therefore, the aim of the present study was to evaluate the effect of androstenedione on cell proliferation, cell death and expression of estrogen receptor (ER) isoforms and proteins related to apoptosis in endometrial cells using two in vitro experimental approaches. Methods The endometrial tissue was obtained from 20 eumenorrheic women [28.7 (25 - 35) years] during the early secretory phase. We analyzed cell proliferation (immunohistochemistry of Ki-67 and spectrophotometric assay); apoptosis (DNA fragmentation (TUNEL) and Annexin V-FITC binding); ER-alpha, ER-beta bcl-2 and bax mRNA abundance (RT-PCR) in explants and isolated endometrial epithelial (EEC) and stromal cells (ESC) incubated with androstenedione 1 micro mol/l (A4) or A4 plus hydroxyflutamide 10 micro mol/l (F) for 24 h. Results In explants, A4 induced an increase of cell proliferation and a decrease on apoptosis in the stromal compartment (p < 0.05). In isolated ESC, proliferation augmented with A4 (p < 0.05), whereas, no significant modifications in the expression of ER-alpha, ER-beta bcl-2 and bax nor in the apoptotic index were observed. In EEC, A4 increase the ER-beta mRNA abundance (p < 0.05) and a decrease of the bcl-2/bax ratio (p < 0.05), without an increase in the apoptotic index. Hydroxyflutamide reverted the effect of androstenedione on the parameters described. Conclusions These results indicate that androstenedione may modulate cell survival, expression of ER-beta and proteins related to apoptosis, suggesting a potential mechanism that associates the effect of hyperandrogenemia on the endometrial tissue.